Time Varying Term Premia and Traditional Hypotheses About the Term Structure. - Longstaff, Francis A (Journal of Finance, 1990)
Empirical evidence of time varying term premia in bond returns is frequently interpreted as evidence against the expectations hypothesis. This paper shows that the expectations hypothesis can actually imply time varying term premia if the time frame for which the expectations hypothesis holds differs from the return measurement period. Furthermore, many of the properties of these term premia are consistent with those of observed term premia. These results are important because they imply that the case against the expectations hypothesis is weaker than claimed in the empirical literature.